Effects of avocado/soybean unsaponifiables (ASU) on the treatment of ligature-induced periodontitis in rats - Oliveira, Guilherme José Pimentel Lopes de; Paula, Luiz Guilherme Freitas de; Souza, João Antônio Chaves de; Spin-Neto, Rubens; Stavropoulos, Andreas; Marcantonio, Rosemary Adriana Chiérici (FapUNIFESP (SciELO), 2017)
The purpose of this study is to evaluate the effect of the avocado/soybean unsaponifiables (ASU) on the treatment of induced periodontitis in rats. Periodontitis was induced in 84 rats via ligature placement around the second upper molar, which was removed after 7 days, and scaling and root planning (SRP) was performed at this time. Subsequently, the rats were randomly allocated to four groups with 21 animals each: One SRP group in which saline solution was administered (SS), and three groups in which ASU was administered (0.6 g/kg/day), beginning either 7 days before the induction of periodontitis (SRP/ASU-7), on the day of periodontitis induction (SRP/ASU0), or on the day of treatment (SRP/ASU+7). ASU and SS were administered daily by gavage until the sacrifice of the animals (7, 15, and 30 days after SRP). The % bone in the furcation area was evaluated by histomorphometry and micro-CT. The expression of proteins (TRAP, RANKL, and alkaline phosphatase) and mRNA (IL-1β, TNF-α, IL-6, RANKL, and alkaline phosphatase) were evaluated by immunohistochemistry and qPCR. The SRP/ASU+7 group presented a higher percentage of bone fill in the furcation area and higher expression of alkaline phosphatase than in the SRP group (at 7 and 30 days, respectively). The SRP/ASU0 and SRP/ASU+7 groups presented lower expression levels of RANKL mRNA than the SRP and SRP/ASU-7 groups at 15 days. ASU administration on the day of the SRP treatment of the ligature-induced periodontitis promoted subtle beneficial effects on periodontal repair following the treatment of induced periodontitis within the experimental period of 7 days.